The low youth motivation for physical training or sports is the problem of healthy lifestyle forming - Kulish N.M; Horodinskiy S.I; Bukoros N.M (Kharkov National Pedagogical University, 2012)
Motivation aspects of physical training and sports are analyzed. The group motivation of three students' teams, where 67 persons are studying, investigated according methodic "The need to achieve the aim" and "Group motivation". It is set the men's need to achieve the aim is much higher then women's, also the men team better motivated for working in the group. All motives are analyzed, the conclusions are set, the reasons of this situation are analyzed. The got results can be used for increasing the motivation of students and pupils. The connection between motivation of sports and healthy lifestyle is reviewed.